COMPUTER PROGRAMS AND PROPOSED REVISIONS OF THE PATENT AND COPYRIGHT LAWS. (Harvard Law Review)
Assesses the need for granting patent law and copyright protection for computer programs, the consequence of protection and possibility of leaving the programs outside both the copyright and the patent system. Discussion on computer programs and programming; Overview of the computer programming industry; Details on copyright, patent and trade secrecy protection for computer programs.